ECONOMIC AND SOCIAL IMPORTANCE OF THE STATE BUDGET - Ayubov I. I.; Amirov T. M. (Scholars Digest Publishing, 2023)
This article talks about the special aspects of state spending, measures to provide financial resources to state sectors, and the content and nature of state spending directly related to the economic, social, political, environmental, management and defense functions of the state.
Keywords: centralized, grant, subsidy, subvention, transfer, decentralized, loan.